PENGARUH PENGETAHUAN WAJIB PAJAK, MODERNISASI SISTEM ADMINISTRASI PERPAJAKAN, DAN SANKSI PAJAK TERHADAP KEPATUHAN WAJIB PAJAK KENDARAAN BERMOTOR (Studi Pada Wajib Pajak Di SAMSAT Jakarta Selatan) - Pradipta Anisa Virgiawati (Monex: Journal of Accounting Research, 2019)
This research is using quantitative study aimed to see whether there are influence of taxpayer knowledge, modernization of taxation administration system, and tax penalties on motor vehicle taxpayer compliance. This study uses the taxpayer who registered in SAMSAT South Jakata as a samples. This research analyzed the questionnaires of primary data from 104 respondends. Sampling technique using incidental sampling. Testing the hypothesis in this study was used Multiple Linear Regression Analysis using SPSS version 25 analysis tool with significant level of alpha 5%. The results of these tests showed that (1) the taxpayer knowledge influence significantly on motor vehicle taxpayer compliance, (2) the modernization of taxation administration system influence significantly on motor vehicle taxpayer compliance, and (3) the tax penalties did not influence significantly on motor vehicle taxpayer compliance. Keywords : taxpayer knowledge, modernization of taxation administration system, tax penalties, and motor vehicle taxpayer compliance.